2020
DOI: 10.1175/wcas-d-19-0011.1
|View full text |Cite
|
Sign up to set email alerts
|

Hurricane Risk Communication: Visualization and Behavioral Science Concepts

Abstract: Increasingly, the risk assessment community has recognized the social and cultural aspects of vulnerability to hurricanes and other hazards that impact planning and public communication. How individuals and communities understand and react to natural hazard risk communications can be driven by a number of different cognitive, cultural, economic, and political factors. The social sciences have seen an increased focus over the last decade on studying hurricane understanding and responses from a social, cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 87 publications
0
25
1
Order By: Relevance
“…The challenge of this project was to develop and deliver products with relevant and actionable drought information to our target audiences, while acknowledging that one-sizefits-all approaches are generally ineffective. Unlike recent literature examining risk communications for hazards such as hurricanes (Millet et al 2020), floods (Percival et al 2020), or sea level rise (Moon et al 2020), we found limited research specific to drought communications and messaging for multiple audiences. Here we discuss the best practices we followed to meet user needs for relevant, clearly written and visualized, and efficiently disseminated drought information, with references to analogous work.…”
Section: Strategies For Enhancing Drought Communicationscontrasting
confidence: 84%
“…The challenge of this project was to develop and deliver products with relevant and actionable drought information to our target audiences, while acknowledging that one-sizefits-all approaches are generally ineffective. Unlike recent literature examining risk communications for hazards such as hurricanes (Millet et al 2020), floods (Percival et al 2020), or sea level rise (Moon et al 2020), we found limited research specific to drought communications and messaging for multiple audiences. Here we discuss the best practices we followed to meet user needs for relevant, clearly written and visualized, and efficiently disseminated drought information, with references to analogous work.…”
Section: Strategies For Enhancing Drought Communicationscontrasting
confidence: 84%
“…This is unsettling because it is often out of the direct control of the weather enterprise-much as epidemiologists and physicians cannot control how people deal with the risks of COVID-19. Efforts to communicate effectively, educate, and persuade stakeholders about the weather take on great importance (Millet et al 2020). Forecasts and warnings are absorbed by people who have experienced the varying and cumulative effects of COVID-19.…”
Section: Evacuation Planningmentioning
confidence: 99%
“…This design also modified the COU by depicting separate maps for watches, warnings, and the cone, while also maintaining the changes in the legend and color schemes of redesign A and expanding the "How to read the map" legend. It is worth noticing that Redesign A and Redesign B were inspired first by a literature review on misinterpretations of uncertainty, confidence, and hurricane forecast products [12]. Another source was the results of several exploratory focus groups conducted between May 15, 2018 and February 13, 2019, recruited through and held at Centro Mater in Little Havana, Catalyst Miami, and Miami Dade College InterAmerican Campus.…”
Section: Prototypesmentioning
confidence: 99%
“…According to metrics provided by the National Hurricane Center's (NHC) [12], its Track Forecast Cone product, commonly known as the "cone of uncertainty" (COU), is the most viewed graphic on the NHC website. The map is commonly used by TV stations and other media organizations [10], and it often appears in social media communications by the NHC and news media.…”
Section: Introductionmentioning
confidence: 99%